Risk Factors Relate to Visual Acuity in School Age Students of Public Primary School (SDN) 07 Pondok Labu South Jakarta (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Vision is one of the most important factors in the education process. Abnormalities of visual acuity in school-age children will impact their achievement. Myopia is appointed by WHO as one priority to restrain and prevent world blindness in 2020. Refraction disorder is third rank (0.14%) of blindness cause in Indonesia after cataract (0.78%) and glaucoma (0.20%). Jakarta itself has a 0.5% incidence of refraction disorder. This study was aimed to discover which factors determined the most to declining visual acuity which caused myopia. This was anobservational analytic study with a cross-sectional design from August – October 2017. The samples were all 144 students of fifth and sixth grade at Public Primary School (SDN) 07 Pondok Labu South Jakarta that compiled the criteria. Bivariate analysis results obtained that relation between risk factors with myopia occurrence with p-value of myopia family history 0.048 [OR=2.17(1.07-4.40)], knowledge 0.961 [OR=0.76(0.29-1.99) and, OR=0.90(0.39-2.05)], attitude 0.947 [OR=0.92(0.46-1.83)], behavior 0.149 [OR=0.43(0.18-1.02) and, OR=0.72 (0.32-1.63)], screen time 1.000[OR=0.99(0.51-1.91)], reading position 0.497 [OR=1.40(0.66-2.99)] dan reading distance 0.283 [OR=2.00(0.71-5.58)]. In conclusion, there was a relation between myopia family history with visual acuity and there was no relation between knowledge, attitude, behavior, screen time, reading position, dan reading distance with visual acuity. The main cause of myopia is the long anteroposterior axis of bulbus oculi that inherited from parents to children.